Perlindungan Hukum Debitur Penanggung Dalam Perjanjian Pembiayaan Terhadap Kumpulan Dengan Sistem Tanggung Renteng(Studi Kasus Pt Mitra Bisnis Keluarga Ventura) - Muhammad Ngiban Hanafi (UIN Sunan Kalijaga Yogyakarta, 2019)
The result of the research shows that the debtorswho use joint and several liability system agreementhave individual assurance, debtors who doinappropriate default of contract and against 1839Indonesian Civil Code article’s. The practice of legalprotection for debtors who have obligation is theprotection through 1839 Indonesian Civil Code article’s,It is not maximally work in protecting the debtors andthe practice of injustice happens between the debtorswho have obligation and the debtors who do default ofcontract. Legal efforts carried out by debtors who bearthe obligations in the joint responsibility system are tohold group members' meetings, collect directly andreport to local village officials with the aim of obtainingcompensation from debtors who conduct defaults.Keywords: Legal Protection, Debitor, Joint and SeveralLiability, and Legal Effort